The interplay between money market development and changes in monetary policy operations in small European countries, 1980 - 2000 - Jens Forssbæck; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2007)
We study the interplay between money market development and changes in monetary policy operating procedures in 11 European countries from c. 1980 up to the launch of EMU. Aspects of money market development such as the size and structure of different market segments, and institutional and regulatory changes, are addressed. We recount and empirically examine the extent of reorientation of monetary policy instruments away from quantitative direct control instruments toward indirect market-based instruments. The process of financial deregulation is uniform across the countries. The path of money market development varies substantially, whereas changes in central bank instruments show both similarities and differences. We hypothesise a relationship between the two processes and provide tentative evidence.
Keywords: E52; E58; G28; N24; 330; Monetary policy operations; Money market; European Union; Deregulation; Geldpolitik; Geldmarkt; Finanzmarktregulierung; Deregulierung; Vergleich; Kleines-Land-Modell; Europa